The Sources for Reconstruction of Piotr Lambin’s Artistic Biography - Elena N. Baiguzina; Elizaveta M. Kolodina (Современные проблемы музыкознания, 2023)
The present article is devoted to analysis of the sources for the reconstruction of the artistic biography of the S. Petersburg-based theater artist Piotr Brisovich Lambin (1862–1923). The research makes use of methods of reconstruction, the biographical and the iconographic method, as well as the method of artistic-stylistic analysis. On the basis of the archival documents of the RGIA (Russian State Historical Archive) the main landmarks of Lambin’s life and artistic activities have been revealed: information about his parents, his christening, his education and academic progress at the Academy for the Arts, his promotion up the career ladder to the position of decorator of the Imperial Theaters during the period from 1885 to 1919, his state awards, his material and family positions. The reference edition “Ves’ Peterburg” [“All of St. Petersburg”] (1895–1916) has made it possible to ascertain the addresses of Lambin’s residences and to reveal that they were situated at close proximity to the Mariinsky Theater. The study of the graphic sources (over 500 sketches by the artist) from various museum funds has made it possible to assemble a list of theatrical productions (of which there are presently 141) on which the master hand worked. An analysis of the sketches makes it possible to come up with the conclusion that Lambin, while being a continuer of the official romantic-academic tradition on the stages of the Imperial theaters, had a responsive approach to the influences of his time, absorbing alternative stylistic tendencies (the Symbolist, the Impressionist, the World of Art trend) which it was not possible to manifest in full measure on the mainstream theatrical stage. The article illuminates for the first time the main landmarks of the paths of life and art of Piotr Lambin, whose legacy has not become an object of academic interest up to the present time. Lambin, undoubtedly, was not in the vanguard of the artistic processes, he pertained to the artists of the “second echelon” without whom the work of the Imperial theaters of the late 19th and the early 20th centuries would be unthinkable.